2016
DOI: 10.1039/c6cc01756h
|View full text |Cite
|
Sign up to set email alerts
|

Tunnelling in carbonic acid

Abstract: The cis,trans-conformer of carbonic acid (H2CO3), generated by near-infrared radiation, undergoes an unreported quantum mechanical tunnelling rotamerization with half-lives in cryogenic matrices of 4-20 h, depending on temperature and host material. First-principles quantum chemistry at high levels of theory gives a tunnelling half-life of about 1 h, quite near those measured for the fastest rotamerizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
(97 reference statements)
2
27
0
2
Order By: Relevance
“…In case of carbonic acid, it was found that tunneling between two conformers has a half-life of approximately 4–20 hours. 33 This is much longer than the time required for the IR measurement of the matrix, which is typically a few minutes. Assuming entropy differences to be negligible for the isomerization process and the energy differences at 0 K representing the enthalpy difference at 210 K, the values in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of carbonic acid, it was found that tunneling between two conformers has a half-life of approximately 4–20 hours. 33 This is much longer than the time required for the IR measurement of the matrix, which is typically a few minutes. Assuming entropy differences to be negligible for the isomerization process and the energy differences at 0 K representing the enthalpy difference at 210 K, the values in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This seems plausible for a gas-phase temperature of 210 K, whereas in the matrix itself at much lower temperatures of 10 K tunneling may play an important role. 33 The half-life against isomerization τ can then be calculated from τ = ln 2/ k . Approximating Δ G ′ with the energy difference, an energy barrier of 7.06 kcal mol –1 results in the half-life of isomer V, τ (V → I) = 9 μs.…”
Section: Resultsmentioning
confidence: 99%
“…CA's chemistry is dominated by its spontaneous breakdown (22) with a first-order decomposition reaction rate constant k dc [corresponding to a decomposition lifetime τ dc = 1/k dc of about 60 ms (20°C)], which is about 300× larger than the pseudo-firstorder back-hydration rate constant k CA (23)(24)(25)(26)(27)(28). CA decomposes via a proton chain mechanism in aqueous solution-and even in the gas phase in the presence of a single water molecule (29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…(26)]. [115] Bemerkenswerterweise sind die beiden Konformere von Kohlensäure auch durch elektrische Entladung in einer CO 2 /Ar-Mischung generiert und durch Mikrowellenspektroskopie charakterisiert worden, [116] und bei der thermischen Zersetzung von Ammoniumbicarbonat wurde ein Massenspektrum von Kohlensäure erhalten. 30 kcal mol À1 fürdie Umlagerung von Hydroxycarben in Formaldehyd lief die Reaktion in den Tieftemperaturmatrices aufgrund des QMT mit einer Halbwertszeit von ca.…”
Section: Angewandte Chemieunclassified
“…[114] Zudem isomerisiert das cis-trans-Rotamer zum cis-cis-Rotamer durch Tu nneln. [115] Bemerkenswerterweise sind die beiden Konformere von Kohlensäure auch durch elektrische Entladung in einer CO 2 /Ar-Mischung generiert und durch Mikrowellenspektroskopie charakterisiert worden, [116] und bei der thermischen Zersetzung von Ammoniumbicarbonat wurde ein Massenspektrum von Kohlensäure erhalten. [117] m-Didehydrobenzol (68)…”
Section: Angewandte Chemieunclassified